Long-term outcomes and predictive factors of achieving low disease activity status in childhood systemic lupus erythematosus: a Chinese bicentric retrospective registered study - Yu, Xi Xi; Deng, Jia; Chen, Qiu Xia; Qiu, Shi Yuan; Jiang, Chao Hui; Wu, Yi Qian; Yang, Qin; Zhang, Gao Fu; Yang, Hai Ping; Zhao, Fei; Li, Qiu; Zhang, Ai Hua; et al. (Frontiers in Immunology, 2024)
Background This study aims to explore the clinical value of low disease activity state (LDAS) in the treat-to-target strategy of pediatric systemic lupus erythematosus (pSLE) and find the risk factors for never reaching LDAS. Methods A total of 272 children with SLE who were diagnosed and followed up in two tertiary hospitals in China during the period from January 2012 to December 2019 were involved in this study, and the clinical presentation, pathology, and treatment were retrospectively studied. Results The male-to-female ratio was 1:5.2, the age at diagnosis was 11.1 years (IQR, 9.8–13.1 years), the disease duration was 1.0 month (IQR, 0.5–2.0 months), and follow-up was 36.5 months (IQR, 25.7–50.9 months). During follow-up, 230 children achieved LDAS, and 42 were never been in. Male (P = 0.018), mucosal ulcer (P = 0.048), liver function damage (P = 0.026), cardiac effusion (P = 0.034), anemia (P = 0.048), urine red blood cells (P = 0.017), urinary leukocytes (P = 0.032), and endothelial cell proliferation in renal biopsy (P = 0.004)—these indexes have statistical differences between the two groups in the baseline. At baseline, endothelial cell proliferation (P = 0.02) is an independent risk factor for never achieving LDAS by multivariate logistic analysis. During follow-up, non-compliance was a risk factor for never achieving LDAS by comparing between groups. Children with biologics achieved LDAS at a higher rate than children without biologics (P = 0.038). The proportion of organ damage in patients never been in LDAS was significantly higher than that in patients who achieved LDAS (P < 0.001). Conclusion Endothelial cell proliferation in renal biopsy and non-compliance during follow-up were independent risk factors for never achieving LDAS. At the end of the follow-up, the organ damage in the remission group was similar to that in the LDAS group, indicating that LDAS can be used as a target for pSLE treatment.